Featured Cover. Issue 1 (6th January 2023) - Yin, Qing; Bi, Ruiye; Li, Haohan; Li, Qianli; Li, Peiran; Wang, Ruiyu; Zhu, Songsong
Abstract : The cover image is based on the Original Article Regulatory role of human fibrocartilage stem cells in condyle osteochondroma by Qing Yin et al., https://doi.org/10.1111/cpr.13342 . Abstract : The cover image is based on the Original Article Regulatory role of human fibrocartilage stem cells in condyle osteochondroma by Qing Yin et al., https://doi.org/10.1111/cpr.13342 .